Ocular injuries from improvised explosive devices - Erdurman, F C (Nature Publishing Group, 2011)
PURPOSE: To document the characteristics, treatments, and anatomical and functional outcomes of patients with ocular trauma from improvised explosive devices (IEDs). METHODS: Retrospective review of ocular injuries caused by IEDs, admitted to our tertiary referral centre. RESULTS: In total, sixty-one eyes of the 39 patients with an average age of 24 years (range, 20–42 years) were included in the study. In total, 49 (80%) eyes of the patients had open-globe and 12 (20%) had closed-globe injury. In eyes with open-globe injury, intraocular foreign body (IOFB) injury was the most frequently encountered type of injury, observed in 76% of eyes. Evisceration or enucleation was required as a primary surgical intervention in 17 (28%) of the eyes. Twenty-two (36%) eyes had no light perception at presentation. Patients were followed up for an average of 6 months (range, 4–34 months). At the last follow-up, 26 (43%) of 61 eyes had no light perception. Postoperative proliferative vitreoretinopathy (PVR) developed in 12 (50%) of the 24 eyes that underwent vitreoretinal surgery, and four of these eyes became phthisical. There were no cases of endophthalmitis. The presence of open-globe injury and presenting visual acuity worse than 5/200 were significantly associated with poor visual outcome (<5/200, P<0.05). In eyes with open-globe injury, the presence of an IOFB was not associated with poor visual outcome (P>0.05). CONCLUSION: Ocular injuries from IEDs are highly associated with severe ocular damage requiring extensive surgical repair or evisceration/enucleation. Postoperative PVR is a common cause of poor anatomical and visual outcome.